1980
DOI: 10.1111/j.1445-2197.1980.tb04502.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Impairment and Its Reversibility Following Variable Periods of Complete Ureteric Obstruction

Abstract: There is debate concerning the time course and degree of r6coveV possible after relief of complete unilateral ureteric obstruction. This study in dogs investigates these features. One ureter was occluded for varying periods, and then reimplanted into the bladder. Recovery was monitored by Tc-Sn-labelled diethylene triarnine penta acetic acid (D.T.P.A.) scans and renograms together with creatinine clearance studies. The morphological changes were also studied. There was found to be a progressive loss of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 9 publications
2
41
0
3
Order By: Relevance
“…Vaughan and Gillenwater [22] indicated that the duration of obstruction is very important in predicting recovery of RF, with only partial recovery to be expected when the obstruction is present for more than 2 weeks in dogs. Two other animal model studies have yielded similar results [23,24]. In 1975, Mayor and co-workers found an advantage in early correction of obstruction, stating that if obstruction was relieved between 1 and 2 years of age, RF improved much less than in children operated on at a younger age.…”
Section: Discussionsupporting
confidence: 52%
“…Vaughan and Gillenwater [22] indicated that the duration of obstruction is very important in predicting recovery of RF, with only partial recovery to be expected when the obstruction is present for more than 2 weeks in dogs. Two other animal model studies have yielded similar results [23,24]. In 1975, Mayor and co-workers found an advantage in early correction of obstruction, stating that if obstruction was relieved between 1 and 2 years of age, RF improved much less than in children operated on at a younger age.…”
Section: Discussionsupporting
confidence: 52%
“…Hinman and Morison [1926] showed in dogs and rats that no repair will take place in a severely damaged hydronephrotic kidney after release of obstruction provided that the contralateral kidney has a normal function. Furthermore, the function of the hydronephrotic kidney shows a dramatic improvement when the contralateral kidney is removed [Fink et al, 1980]. Recently, it was hypothesized that when renal function decreases in the hydronephrotic kidney due to ongoing obstruction, the contralateral non-obstructed kidney is stimulated to grow at a fast rate.…”
Section: Compensatory Growth In the Contralateralmentioning
confidence: 98%
“…A progressive loss of functional recovery has been reported with increasing periods of obstruction. In dogs, a nearly complete return of function follows correction, after 4 days of obstruction [Fink et al, 1980]. After 14 days of obstruction, the GFR and tubular function returned to 46% of the control levels by 4 months after relief of obstruction, and no changes were seen thereafter [Vaughan et al, 1971].…”
Section: Duration Of Obstructionmentioning
confidence: 98%
“…Healthy dogs subjected to 1 week of ureteral obstruction recover 65% of the baseline glomerular filtration rate (GFR) and recovery plateaus after a period of 5 weeks [5]. After 2 weeks of ureteral obstruction, GFR returns to 46% over a period of 4 months [6,7].…”
Section: Introductionmentioning
confidence: 99%